The Obamas: Intersectional Interventions, Transnational Tryouts (KULT_online, 2012)
This timely volume emerged out of the conference "Obama and the Paradigm Shift", organized in the summer of 2011 at the University of Giessen, and offers 10 essays that ask if and to what extent Barack and Michelle Obama caused a paradigm shift in the U.S. and Germany in terms of gender, race, and political divisiveness. Despite not always being consistent, especially not in terms of its self-declared transcultural approach, this collection of essays offers lively, differentiated, multifaceted, and critical readings of the presidency of the Obamas. As such, it provides enrichment for the current, deeply polarized book market on the Obamas.